A Program of Research to Evaluate the Impact of Deceased Organ Donation Legislative Reform in Nova Scotia: The LEADDR Program. Issue 1 (January 2021) - Weiss, Matthew J.; Krmpotic, Kristina; Cyr, Tim; Dhanani, Sonny; Dieudé, Mélanie; Dirk, Jade S.; Hartell, David; Isenor, Cynthia; James, Lee; Lucas, Amanda; Patriquin, Chelsea; Simpson, Christy; et al.
Abstract : Background: This is the first time deemed consent, where the entire population of a jurisdiction is considered to have consented for donation unless they have registered otherwise, will be implemented in North America. While relatively common in other regions of the world—notably Western Europe—it is uncertain how this practice will influence deceased donation practices and attitudes in Canada. Methods: We describe a Health Canada funded program of research that will evaluate the implementation process and full impact of the deceased organ donation legislation and the health system transformation in Nova Scotia that includes opt-out consent. Results: There is a need to evaluate the impact of these changes to inform not only Nova Scotia and Atlantic Canada, but also other provincial, national, and international stakeholders. Conclusions: We establish a rigorous academic framework that we will use to evaluate this significant health system transformation. Abstract : Supplemental Digital Content is available in the text.